Peningkatan Aktivitas Materi Induksi Magnet Melalui Model Pembelajaran Team Assisted Individualization Pada Siswa Kelas XII MIA 3 SMAN 2 Pontianak - ., Udhzaenah . (Universitas Tanjungpura, 2017)
This research purposed to increase students learning activities of XII MIA 3 students of SMA Negeri 2 Pontianak on magnetic induction materials. This research consist of 2 (two) cycles with each meeting takes time 3x45 minutes. Each cycle consisted of planning, implementation, observation, and analysis section.. To get class management and learning activities data, teacher and student’s observation sheet was used. The results showed that application of cooperative learning model Team Assisted Individualization can improve student’s activities in class XII MIA 3 SMA Negeri 2 Pontianak on magnetic induction material from 45 activities in the first cycle to 70 activities in the second cycle.